CONCEPTION RATE OF ARTIFICIAL INSEMINATION OF BALI CATTLE ON DIFFERENT SEMEN DEPOSITIONS - Firmiaty, Sri; Idrus, Muhammad; Amiluddin, Amiluddin; Sudirman, Sudirman; Sonjaya, Herry; Suyadi, Suyadi; Iskandar, Hikmayani (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
This study aims to analyze the pregnancy rate resulting from artificial insemination of Bali cattle with different semen depositions. The research method used was a field experiment with three treatments: semen deposition at positions 3, 4, and 4+ (right side/dexter side). Pregnancy rate data were evaluated through Non-Return Rate (NRR1 and NRR2), Service per Conception (S/C), and Conception Rate (CR). The study was conducted on 120 Bali cattle in Bulukumba District, South Sulawesi. The results showed an increase in NRR in semen deposition 3, 4, and 4+ during the observation period of NRR 31 – 60. Although some breeders reported arousal symptoms late, the increase in NRR indicates a good understanding of arousal detection. Semen deposition at position 3 produces the lowest NRR, which can be caused by reproductive function abnormalities, silent heat, endometritis, or late reporting by farmers. The results of the S/C evaluation showed the lowest value and the highest of CR at semen deposition 4, which means that the semen deposition was closer to the fertilization site. Semen deposition at positions 4+ on dexter side althrough closer to the fertilization site was lower results of CR than posisition 4, because sperma only toward in right tubafolopii. The effectiveness of AI is significantly impacted by accurately detecting and timing the insemination process based on the ovulation period. This study provides important information regarding AI techniques in Bali cattle that can be used to increase the population and genetic quality of beef cattle in Indonesia.